2015
DOI: 10.1515/pjvs-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid metabolism during last month of pregnancy and first two months of lactation in primiparous cows – analysis of apolipoprotein expression pattern and changes in concentration of total cholesterol, HDL, LDL, triglycerides

Abstract: The final weeks of pregnancy and period of increasing lactation abound with adaptive changes in the intensity of metabolic processes. Maintaining the homeostasis of an organism in prepartum and postpartum periods is the key condition in maintaining the health of the mother and the fetus/calf. The aim of the study was to analyze physiological changes in lipid metabolism in cows during the last month of first pregnancy and in the first two months of lactation, based on the expression of identified apolipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
5
13
0
2
Order By: Relevance
“…The pathogen isolation rate increased 2.1% per unit (mg dL -1 ) increase in serum tryglicerides. Interestingly, Kushibiki et al (2002) studied the effect of tumor necrosis factor-alpha (TNF-α) on the lipid metabolism of heifers, and they observed that infusion with recombinant TNF-α quickly increased their trygliceride concentrations 0.5 hours after infusion. Regarding that, TNF-α plays a key role in regulating an inflammatory immune response, and it mediates hypertriglyceridemia in response to infection (Bradford et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen isolation rate increased 2.1% per unit (mg dL -1 ) increase in serum tryglicerides. Interestingly, Kushibiki et al (2002) studied the effect of tumor necrosis factor-alpha (TNF-α) on the lipid metabolism of heifers, and they observed that infusion with recombinant TNF-α quickly increased their trygliceride concentrations 0.5 hours after infusion. Regarding that, TNF-α plays a key role in regulating an inflammatory immune response, and it mediates hypertriglyceridemia in response to infection (Bradford et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The function of cholesterol is to build cell membranes and to produce different hormones essential for proper body functions such as estrogen, progesterone and aldosterone (Ahmad et al, 2004). By assessing the parameters such as the total cholesterol, HDL (High density lipoprotein), LDL (Low density lipoprotein) and triglycerides (TG), variations in lipid metabolism occurring in lactating cows could be better understood (Kurpińska et al, 2015). Aspartate transaminase (AST), Alanine transaminase (ALT) and Gamma-glutamyltransferase (GGT) are serum enzymes commonly found in the liver tissues and are considered as biological health markers in case of hepatic disorders and other health issues (Boonprong et al, 2007;Lim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, triglycerides (TAG) and NEFA are both associated with fatty liver (Bobe et al 2004) and an increase in postpartum liver TAG concentrations is accompanied by an increase in plasma NEFA concentrations (van den Top et al 1995). Besides cholesterol and TAG, high-density lipoproteins (HDL) are related to the lipid metabolism during the transition period (Kurpinska et al 2015).…”
mentioning
confidence: 99%